IDE SEKULARISASI THOHA HUSEIN - Ghozali, `H.M. Yunus (Al Qalam, 1998)
At the beginning of the 20th century, there were many statement/ideas declared by moslem scientist in Islamic world. Some of the ideas were from Thoha Husein. Unfortunately, only few people who concerned about it. Most people, especially moslem, tend to avoid the ideas which is not suit with development then.Nowadays, at the end of the 20th century, people back to Islam. Many_ people began to learn and gain knowledge of Islam . Its ideas and tradition start to be applied as a way of li fe. This phenomena is organized by moslem scientist movement. The impact are in every places and society. Not only in social institution such as mosque, schooletc, but also in the offices and social organization. The changes show that people still beleve in Islam. So that the people especially moslem scientist, realize and concern about the commitment, discipline and Islamic education . They want Islam to be applied in real life.When people back to Islam, they start to analyze and use the ideas of moslem scientist, including Thoha's ideas. And as ideas, Thoha's statement are not always right and absolute. Its changeable. The ideas is opened for criticism. And this is something great that we can find in Islam. As long as still hold in the principles of Islam, everybody free to express their idea. And alÂthough there are many different opinion and ideas but we see it as one, "Unity and Diversity ".